Endless connections : New Zealand secular intentional rural communities founded in the 1970s : a thesis submitted in fulfilment of the requirements for the degree of Master of Arts in History at Massey University - Jenkin, Robert (Massey University, 2012)
Abstract not available.
Keywords: Collective settlements; Communal living; New Zealand; History